Revision of Spinosphaera and establishment of the new genus Hutchingsiella (Polychaeta: Terebellidae: Terebellinae) - Londoño-Mesa, Mario H. (Journal of the Marine Biological Association of the UK, 2003)
Spinosphaera is a Terebellinae genus with three species described from the Pacific Ocean, S. pacifica from Japan, S. oculata from California, and the doubtful S. cowarrie from Western Australia. The genus is presently unknown in the Grand Caribbean region. Spinosphaera is characterized by the absence of branchiae, by the great number of notopodia, and the presence of a special type of notochaetae, called ‘Spinosphaera-chaeta’. These chaetae have three different regions: distal denticulate blade, neck separating the former from a middle swollen spinous region, and a proximal smooth or bilimbate region; two sizes are present. The genus is redefined, with redescription of all species currently known. Three new species are described here, two from the Mexican Caribbean coast, S. hutchingsae and S. carrerai, and one from California, S. harrisae. A taxonomic key to identify all species is given. Hutchingsiella gen. nov. is proposed for S. cowarrie; it differs from Spinosphaera in having notochaeta from segment 5 and neurochaetae from segment 6, and for lacking Spinosphaera chaeta.
World Polychaeta Database (WPolyD)